S2_6_Artifical_Gravity_v2 - Hutchinson, James; Tebbs, Emma; Comyn-Platt, Edward (Physics Special Topics, 2009)
This paper looks into the use of a rotating crew capsule to generate an acceleration equal to that caused by the Earth’s gravity. This will help to overcome some of the problems, especially medical, from long duration spaceflight in microgravity. It discusses some of the difficulties and limitations of such a system, pointing out places where technologies will have to improve.